A simple route to prepare Fe3O4@C microspheres as electromagnetic wave absorbing material - Adebayo, L.L. (Elsevier Editora Ltda, 2021)
To tackle the problem of electromagnetic (EM) pollution and the adverse effect of EM interference, tremendous research works have been aimed at the realization of the optimal EM wave absorbing materials. In this study, Fe3O4@C microspheres with a regular size of 5-7 Î¼m were prepared via a simple hydrothermal process and subsequent high-temperature calcination. The carbon microspheres were produced from the pyrolysis of a carboxyl and carbohydrate group. The Fe3O4@C microspheres are made up of Fe3O4 nanoparticles entangled with even distribution on the carbon microsphere. The Fe3O4@C microspheres displayed a good BET surface area (181.89 m2/g). A Fe3O4@C-30 sample exhibited a minimum reflection loss value of -47 dB at 16.89 GHz, with 2.0 mm matching thickness. Large amounts of EM waves transmit through the material due to favorable impedance match at the Fe3O4@C microspheres air interface, this resulted in low reflections of the EM waves at the boundary. Â© 2021 The Author(s).